One-pot synthesis, characterization and polymerization of hyperbranched benzoxazine resins derived from A2+ B3 monomers. (December 2019) - Cai, Wan-an; Zegaoui, Abdeldjalil; Zhang, Li-li; Dayo, Abdul Qadeer; Ghouti, Hamid Abdelhafid; Wang, Jun; Liu, Wen-bin; Tang, Tao
Abstract: Herein, we have designed and synthesized two series of novel hyperbranched benzoxazines (HBs), namely HB-TA6, HB-TA12, HB-TAF6 and HB-TAF12, derived from Jeffamine T-403, bisphenol-A/bisphenol-AF, and p- formaldehyde via the simple one-step Mannich condensation reaction. Their feature structures (ArCH2 N and OCH2 N) were characterized using the Fourier transform infrared spectroscopy (FTIR), proton, and carbon nuclear magnetic resonance ( 1 H NMR and 13 C NMR) analyses. The number-average molecular weights ( M n ) and weight-average molecular weights ( M w ) of HBs were in the range of 4700–6000 and 9700–11700 Da, respectively, which showed good solubility in common organic solvents at room temperature. The differential scanning calorimeter (DSC) was used to investigate the polymerization behavior and curing kinetics of these new HBs, and the obtained results indicated that all the HBs performed the lower temperature of exothermic peaks and activation energy values compared with the conventional phenol-aniline based benzoxazine (P-a). The thermal properties of cured polymers were evaluated by thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA) showing the char yield ( Y c ) and glass transition temperature ( T g ) in the range of 18.6–30.5% and 157–164 °C, respectively.